Greenhouse gas emission calculation and energy impact of TPS3R flamboyan using waste reduction model (WARM) V.15: Implications for disaster risk reduction - Maulidia, Asrining Ghina; Wikaningrum, Temmy (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Human activities contribute to increased greenhouse gas concentrations, such as CO₂ and CH₄, which intensify the greenhouse effect and elevate Earth's temperature. TPS3R Flamboyan aims to reduce plastic waste through recycling, composting, and landfilling at TPA Cipeucang. While these processes help reduce waste, they can also produce CO₂ emissions. This study evaluates the CO₂ emissions from the baseline waste management scenario and compares it with an alternative scenario using the Waste Reduction Model (WARM) to assess GHG emissions and energy use. Methods: Data was collected in June 2020 from TPS3R Flamboyan and TPA Cipeucang in South Tangerang, analyzing waste types and GHG emissions using the WARM software. The study utilized baseline and alternative waste management scenarios to assess CO2 emissions and energy use, with input data on various waste types such as food waste and plastics. WARM compared the emissions and energy use for each scenario, providing insights on GHG reductions and energy efficiency in waste management practices. Findings: Total GHG emissions from baseline MSW generation and management (MTCO2E) is -2.23 and total GHG emissions from alternative MSW Generation ad management (MTCO2E) is -4,46. Total Energy use from baseline MSW Generation and Management (million BTU) is -33.98 and total Energy use from alternative MSW generation and Management (million BTU) is -92.22. Conclusion: Both scenarios indicate that the alternative scenario results in a higher reduction of emissions compared to the baseline management. This demonstrates the effectiveness of the alternative waste management practices in reducing greenhouse gas emissions. Novelty/Originality of this article: This research provides a novel approach by using the Waste Reduction Model (WARM) application, developed by the U.S. Environmental Protection Agency (EPA), to estimate greenhouse gas emissions and energy use in municipal solid waste management scenarios. This application offers high-level estimates for emissions reduction and energy efficiency, providing valuable insights for waste management practices.